Kant nella riflessione psichiatrica sulla schizofrenia - Costantini, Marco (B@belonline, 2021)
This contribution retraces the most significant moments of a debate that has seen researchers from different disciplinary areas reflect on schizophrenia, in particular on the symptom of thought insertion, with the conceptual tools of Kant’s theoretical philosophy. In the course of this report, some problematic aspects of the interpretations of the Critique of Pure Reason promoted in the aforementioned debate are highlighted. The last part of the contribution presents some considerations on the relationship between critical philosophy and madness.